Разработка функциональной части грузоперевозчика для персонального сайта грузоперевозок - Стрименешенко, А. С.; Шалимов, А. А. (ХНУРЕ, 2019)
Currently, websites and web resources are developed using many software tools and various programming languages. Customer needs are growing and product technology is evolving in parallel. With the help of the web, the provision of various types of services is simplified, and time is also significantly saved. The purpose of my work is a personal website to provide the carrier with the opportunity to choose an order (cargo) for cargo transportation, as well as to place information about your route and information about the car so that the client who needs to transfer cargo can view and order the freight that satisfies his requirements.